2022
DOI: 10.3389/fmicb.2022.882422
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of blaCTXM–1/IncI1-Iγ/ST3 Plasmids in Extended-Spectrum β-Lactamase-Producing Escherichia coli Isolates Collected From Domestic Animals in Guadeloupe (French West Indies)

Abstract: Extended-spectrum β-lactamase-producing Enterobacteriaceae (ESBL-E) have been classified in the group of resistant bacteria of highest priority. We determined the prevalence of ESBL-E collected in feces from household and shelter pets in Guadeloupe (French West Indies). A single rectal swab was taken from 125 dogs and 60 cats between June and September 2019. The prevalence of fecal carriage of ESBL-E was 7.6% (14/185, 95% CI: 4.2-12.4), within the range observed worldwide. The only risk factor associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…This study investigates the origin of ESBL E. coli in a farm of food-producing animals not exposed to third-generation cephalosporins, allowing the identification of a local cattle and fly reservoir of E. coli ST3268/bla CTX-M-15 /bla TEM-1B . This ST was not found elsewhere in Guadeloupe (Sadikalay et al, 2018;Guyomard-Rabenirina et al, 2020;Gruel et al, 2021Gruel et al, , 2022. This ST was also rarely found in genomic databases.…”
Section: Discussionmentioning
confidence: 59%
“…This study investigates the origin of ESBL E. coli in a farm of food-producing animals not exposed to third-generation cephalosporins, allowing the identification of a local cattle and fly reservoir of E. coli ST3268/bla CTX-M-15 /bla TEM-1B . This ST was not found elsewhere in Guadeloupe (Sadikalay et al, 2018;Guyomard-Rabenirina et al, 2020;Gruel et al, 2021Gruel et al, , 2022. This ST was also rarely found in genomic databases.…”
Section: Discussionmentioning
confidence: 59%
“…Nevertheless, we found that there were major epidemics in different cities, for example, the major epidemics of ESBL E. coli in Shenyang was CTX-M-1, while in Tangshan it was CTX-M-15. Combined with previous studies in a number of other countries, ESBL E. coli was found to be endemic to CTX-M-1 in France, OXA-48 in Switzerland, and CTX-M-8 in Brazil [26][27][28]. Therefore, we revised our former hypothesis: the prevalence does depend on geography, and the type of epidemic is geographical.…”
Section: Discussionmentioning
confidence: 78%
“…The island has faced the emergence of nosocomial infections associated with carbapenemase-producing Enterobacteriaceae since 2014 and also a high incidence of nosocomial infections caused by ESBL-producing Enterobacteriaceae [9][10][11][12]. Environmental investigations have focused on the faecal carriage of ESBL-producing Enterobacteriaceae in domestic animals [13,14], farm animals [15], and wildlife [16,17] and also on the transmission of clinical strains to the environment [8,18]. Antibiotic resistance was also studied in effluents from wastewater treatment plants (WWTP) and in surface waters with or without such discharges [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotic resistance was also studied in effluents from wastewater treatment plants (WWTP) and in surface waters with or without such discharges [18,19]. Although these studies concluded that there is limited circulation of antibiotic-resistant bacteria (ARB) between humans and the environment [8,13,16,18], there are still gaps in understanding the transmission of ARB from the environment to humans.…”
Section: Introductionmentioning
confidence: 99%